Structural characterization of three RNA hexanucleotide loops from the internal ribosome entry site of polioviruses - Klinck, Roscoe; Sprules, Tara; Gehring, Kalle (Nucleic acids research, 1997)
Structural characteristics of three RNA hairpins from the internal ribosome entry site of poliovirus mRNAs have been determined in solution by NMR. Complete proton, phosphorus and carbon resonance assignments were made for the three 16 nt hairpins. The loop sequences, 5′-AAUCCA, AAACCA and GAACCA, have been shown to be essential for viral mRNA translation. NOESY spectra for the three oligomers were very similar indicating a common three dimensional structure. Stems were A-type duplexes with C3′-endo sugar pucker. In the loops, sequential base stacking interactions were detected for all bases except between U8/A8 and C9, indicating a turn in the phosphodiester backbone at this point. Only one nucleotide, U8/A8, had a sugar pucker which deviated appreciably from C3′-endo. The final base in the loop, A11, exhibited an unusual gauche(−) gamma angle. An ensemble of 10 structures calculated for one hairpin using restrained molecular dynamics shows that the first three bases of the loop are turned so as to be exposed to the exterior of the molecule, while the remaining three bases are in an orientation approximating a continuation of the stem helix. Structure calculations and NMR relaxation measurements indicate that the loop apex is subject to considerable local dynamics.